2005
DOI: 10.7202/705573ar
|View full text |Cite
|
Sign up to set email alerts
|

La lagune de Ghar El Melh : Diagnostic écologique et perspectives d'aménagement hydraulique

Abstract: La lagune de Ghar El Melh, située au Nord de la Tunisie (dans le Golfe de Tunis), est caractérisée par une superficie de 28,5 km2, une faible profondeur et une faible communication avec la mer. Actuellement, sous l'effet des actions anthropiques (les rejets terrestres), elle connaît une dégradation progressive de la qualité de ses eaux et sédiments dont les conséquences sont la chute de la richesse biologique et la réduction des ressources halieutiques de la lagune. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 2 publications
(1 reference statement)
2
22
0
1
Order By: Relevance
“…It was surprising to discover that all the five optical classes were present in the lagoon, giving rise to a consistent spatial heterogeneity, not detected by classical optical methods. The spatial distribution of classes was consistent with the results from OASs analysis and with previous data on lagoon hydrodynamics (Moussa et al, 2005;Thompson et al, 2009). As shown in Fig.…”
Section: Optical Propertiessupporting
confidence: 81%
See 1 more Smart Citation
“…It was surprising to discover that all the five optical classes were present in the lagoon, giving rise to a consistent spatial heterogeneity, not detected by classical optical methods. The spatial distribution of classes was consistent with the results from OASs analysis and with previous data on lagoon hydrodynamics (Moussa et al, 2005;Thompson et al, 2009). As shown in Fig.…”
Section: Optical Propertiessupporting
confidence: 81%
“…Waters were classified as M in the North of the basin, where marine influence was still acting and the small fishermen's village produced reduced impacts, quickly turning to V where the depths decreased, permitting to wind to raise sediments from the bottom (Moussa et al, 2005;Thompson et al, 2009), and where inputs from cultivated lands were stronger. Briefly, a relation was observed between the types of human activities and the achieved optical classification.…”
Section: Discussionmentioning
confidence: 99%
“…This counteracts the effects of a reduction of the load from the land. Several authors have suggested increasing the water exchange between the lagoon and the sea as a measure to improve the water quality in the lagoon (Shili et al, 2002;Moussa et al, 2005). The present investigation and model scenarios show that the water quality at the boundary can not be ignored.…”
Section: Coastal Boundary Concentrationsmentioning
confidence: 71%
“…Due to a combination of coastal contours and alluvium deposits from the Medjerda River, this small gulf has been progressively cut off from the Utique Sea, causing the lagoon to take on its present morphology. A channel, called El Boughaz (70 m wide, 1.5-2.5 m deep), has been dredged through the sand bars that separate the lagoon from the Mediterranean, providing a permanent water outlet to the sea (Moussa et al, 2005), though at times of high water additional connections appear . Coastally located in the northern part of the Gulf of Tunis (37°06 0 N, 10°11 0 E) between Ras Tarf (Cape Farina) and the estuary of the Medjerda River, GML consists of a complex of three wetlands: the main lagoon or El Bhira (meaning ''the small sea'' in Arabic, 26.7 km 2 ); Sebkhet El Ouafi (5.2 km 2 ) in the southeast; and Sebkhet Sidi Ali El Mekki (3.7 km 2 ) in the northeast ).…”
Section: Study Sitementioning
confidence: 99%